Akad al-Ijarah al-Mausufah fi al-Dzimmah in Sharia Banking in Aceh: A Study of Homeownership Finance - Zubir Zubir; Muhazir Muhazir; Zulham Wahyudani (Justicia Islamica, 2022)
This paper aims to analyze the al-Ijarah al-Mausufah fi al-Dzimmah contract model and its application to Islamic Banking. So far, the paradigm that has developed regarding homeownership financing contracts (PPR) is to use Murabahah or Musyarakah Mutanaqisah (MMQ) contracts. In practice, the results of housing built are often not by the previously agreed contract. This is a dilemma for Customers because, on the one hand, the down payment has been given, and the payment process has been carried out. In these conditions, applying the al-Ijarah al-Mausufah fi al-Dzimmah (IMFZ) contract is essential to protect the rights of Customers which have been neglected. The al-Ijarah al-Mausufah fi al-Dzimmah contract requires the cancellation of the contract from the Customer if the reality and the contract made with the Bank do not match. This research is non-doctrinal with a conceptual approach. The conceptual approach is used to analyze theoretically and practically the use of the al-Ijarah al-Mausufah fi al-Dzimmah contract. The study results show that Islamic Banking in Aceh has not used the IMFZ contract. This is because of first, the lack of understanding of the contract from both the Bank and the Customer; second, the tendency of the public and Banks to use Murabaha contracts than other contracts because Murabahah contracts are easier to understand and commonly used, so far; third, Banks and Developers will face more significant risks when using al-Ijarah al-Mausufah fi al-Dzimmah contracts than Murabahah and Musyarakah contracts. The IMFZ contract requires the Bank, Developer, and Customer to collaborate to supervise house construction to avoid default. Using the al-Ijarah al-Mausufah fi al-Dzimmah contract will minimize fraud and gharar committed by the Developer against the Customer. This article contributes to Customers and Banks in maintaining quality in housing finance which Developers often overlook.